2010
DOI: 10.4314/ijhr.v2i4.55431
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial characteristics of patients admitted to a drug rehabilitation unit in Nigeria

Abstract: an online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[ 17 ] It has also been widely used in previous studies in this environment. [ 18 19 ] The categories are as follows: Group I consists of professionals with university degrees, e.g., doctors, lawyers, scientists, etc. ; group II consists of professionals without university degrees and include teachers, administrators, large scale farmers, and armed forces officers; group III consists of clerks, motor vehicle drivers, mechanics, etc.…”
Section: Methodsmentioning
confidence: 99%
“…[ 17 ] It has also been widely used in previous studies in this environment. [ 18 19 ] The categories are as follows: Group I consists of professionals with university degrees, e.g., doctors, lawyers, scientists, etc. ; group II consists of professionals without university degrees and include teachers, administrators, large scale farmers, and armed forces officers; group III consists of clerks, motor vehicle drivers, mechanics, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Other substance of abuse includes passion energy drink and benzhexol (anticholinergic effect). study, also, Eze et al (2009) reported high level of unemployment in their study. Sampling bias and operation classification of employment status may explain the discrepancies observed in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…This finding is also supported by Abayomi et al (2012) who found a mean age of 31.8 in their study and reported that most of their participants were males, and never married. Similarly, Eze et al (2009) reported most of their respondents to be male, single and unemployed. However, the discrepancies here is between educational attainments and employment status of the participants in this present study, 50% attended secondary school education and 40.4% attended tertiary education making a total of 90.4% while Abayomi et al (2012) reported that 61.9% had less than secondary school education in their Note: Current use of substance is the usage within the last three month as categorized by World Health Organization (WHO) using ASSIST Questionnaire.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation